2003
DOI: 10.1590/s0103-90162003000200009
|View full text |Cite
|
Sign up to set email alerts
|

Competitivity of the common-bean plant relative to the weed alexandergrass [Brachiaria plantaginea (link) hitch.]

Abstract: Methodologies of competitive interaction quantification between weeds and crops are not widely elucidated and compared in the literature. The competitive ability of common-bean (Phaseolus vulgaris) relative to alexandergrass (Brachiaria plantaginea) was assessed and two approaches of replacement series experiment analysis were compared. The response of the species to the presence of each other at different densities and proportion was evaluated. Replacement series at total densities of 625, 816 and 1,111 plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
7
0
6
Order By: Relevance
“…Passini, Christoffoleti and Yada (2003) observed that intraspecific competition was more important in Phaseolus vulgaris than in Brachiaria plantaginea because the competitiveness of the crop was superior to that of the weed. Cultured sorghum showed superior competitive ability compared with Sorghum halepense (Hoffman;Buhler, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Passini, Christoffoleti and Yada (2003) observed that intraspecific competition was more important in Phaseolus vulgaris than in Brachiaria plantaginea because the competitiveness of the crop was superior to that of the weed. Cultured sorghum showed superior competitive ability compared with Sorghum halepense (Hoffman;Buhler, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…No experimento I, em série aditiva, foram avaliados monocultivos de C. difformis suscetível a herbicidas inibidores de ALS (oriundo de Itajaí no Estado de Santa Catarina) e arroz, cultivar BRS Querência, com o objetivo de determinar a população de plantas m -2 a partir da qual a área foliar (AF) e a matéria seca da parte aérea (MSPA) por unidade de área tornam-se independentes da população, de acordo com a "lei de produção final constante" (Radosevich et al, 1997 ) foram analisadas aos 40 dias após a emergência (DAE). A AF foi determinada com auxílio de determinador de AF Modelo 3100C e a MSPA foi quantificada pela pesagem da parte aérea das plantas após secagem em estufa a 60° até massa constante.…”
Section: Methodsunclassified
“…Os índices CR, K e C foram considerados diferentes, quando no mínimo em duas proporções, ocorressem significâncias pelo teste t (Bianchi et al, 2006). Para análise estatística da PR, primeiro foram calculadas as diferenças para os valores de PR obtidos nas proporções de 25%, 50% e 75% de plantas, em relação aos valores pertencentes às retas hipotéticas obtidas nas respectivas proporções (Passini et al, 2003). O teste t (p≤0,05) foi utilizado para testar as diferenças nos índices estimados em relação à reta hipotética (Passini et al, 2003;Hoffman e Buhler, 2002).…”
Section: Methodsunclassified
See 2 more Smart Citations